(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explore the various innovative teaching methods available that tertiary institutions in Nigeria can adopt to enhance students engagement. The paper used secondary data. The secondary data were collected from both print and online publications. Content analysis was used to analyze the selection of literature for the study. The paper concludes that interactive lessons, virtual reality technology, AI in Education, blended learning, 3D Printing, design-thinking process, project-based learning (PBL), inquiry-based learning, jigsaw, cloud computing teaching, flipped classroom, peer teaching, peer feedback, crossover teaching, personalized learning, active learning, gamification, problem-based learning, mistake-led teaching and collaborative learning as some of the innovative teaching methods available that tertiary institutions in Nigeria adopt to enhance students engagement. Based on this findings, the paper recommend that tertiary institutions management should encourage the academic staff to adopt any of the innovative teaching strategies that suit their teaching and learning environment. Also, the management of tertiary institutions in Nigeria should constantly organize capacity building for academic staff on innovative teaching methods and how the methods can be used in the various institutions.